2020
DOI: 10.35535/pfsyst-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Testing DNA barcoding in Usnea (Parmeliaceae) in Colombia using the internal transcribed spacer (ITS)

Abstract: We tested the functionality of ITS-based DNA barcoding in lichen fungi using Colombian samples of the genus Usnea as an example. New ITS sequences were generated for 15 samples from five localities in two different ecoregions, representing varying morphologies and medullary chemistries. We employed five strategies to identify the samples: (1) BLASTn on the NCBI BLAST site with the original identifications of the best matching reference sequences; (2) as previous, but with revised identifications of the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The standard DNA barcoding marker—the ITS—has been a powerful tool for understanding species diversity in lichen‐forming fungi (Lücking et al, 2020 ; Schoch et al, 2012 ), although issues with using this marker in some clades have been demonstrated (Pino‐Bodas et al, 2013 ). In taxonomically challenging groups, the ITS can provide an important first pass for grouping closely related species (Leavitt et al, 2013 ; Lücking et al, 2014 ; Moncada et al, 2020 ). While the taxonomic implications of DNA barcoding approaches remain unsettled (see Meier et al, 2021 ), our results show that species partitions inferred from the ITS marker coincide with clades comprised of closely related species‐level lineages in Niebla inferred from phylogenomic data (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The standard DNA barcoding marker—the ITS—has been a powerful tool for understanding species diversity in lichen‐forming fungi (Lücking et al, 2020 ; Schoch et al, 2012 ), although issues with using this marker in some clades have been demonstrated (Pino‐Bodas et al, 2013 ). In taxonomically challenging groups, the ITS can provide an important first pass for grouping closely related species (Leavitt et al, 2013 ; Lücking et al, 2014 ; Moncada et al, 2020 ). While the taxonomic implications of DNA barcoding approaches remain unsettled (see Meier et al, 2021 ), our results show that species partitions inferred from the ITS marker coincide with clades comprised of closely related species‐level lineages in Niebla inferred from phylogenomic data (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences intended to be submitted as DNA barcodes should only include the generally used region for that marker in order to allow BLAST searches to work optimally. For example, submissions for the ITS region (Schoch et al 2012) should be submitted with only short SSU and LSU flanking sequences (Moncada et al 2020). b.…”
Section: Describing New Speciesmentioning
confidence: 99%
“…Such databases facilitate quick determination of taxa based on DNA sequences, but are of limited use since the identification using a simple blast search of a single marker may bias the recognition of genetically similar species (e.g. Lücking et al 2020b;Moncada et al 2020). Furthermore, numerous records are mislabelled in GenBank, as recently reported by Hofstetter et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Although BLAST searches facilitate quick determination of taxa based on DNA sequences, the recognition of genetically similar species may be challenging (e.g. Lücking et al 2020a, b;Moncada et al 2020).…”
mentioning
confidence: 99%